Pengaruh Tingkat Pendidikan Orang Tua Dan Implikasinya Terhadap Pola Asuh Pendidikan Anak Usia Dini Di RA ARROFROF - Tamara Shoppia; Ichsan Ichsan; Winarti Winarti (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2022)
Education is important in every element of human life, parenting style is a series of actions taken by parents, in fact in Indonesia most of them still refer to the education level of parents and some refer to previous parenting patterns. The place of this research is located at the RA ROFROF school, Kec. Kelapa Dua, the location was chosen as the research location because this school has been a place for researchers to teach since 2019. The research method used in this case is a qualitative method, in this study the data obtained include words or stories directly from research informants. The results of the interview research conducted at the RA ARROFROF school indicate that there are several factors that can influence parenting patterns for children, including: 1) Economic factors, 2) Education factors and 3) Age factors. The conclusions of this study show the results: 1) The understanding possessed by parents at the ARROFROF school about the importance of early childhood education is in the fairly good category